Perspectives : Research and Tips to Support Science Education, K-6. - Hanuscin, Deborah (National Science Teachers Association, 2013)
Here's a time-saving way to learn what research tells you about teaching elementary science and applying the findings both inside and outside your classroom. It's a collection of 27 ""Perspectives"" columns from Science and Children, NSTA's award-winning elementary-level journal. The book is organized in six science-specific sections, including general teaching goals, strategies to facilitate learning, student thinking and misconceptions, and your own professional development. The columns are written to make it easy to grasp the material and then use what research tells you about issues of spe.